Retracted: Perhitungan Neraca Panas dan Neraca Massa pada Proses Produksi Pelumas di PT. X di Tambun Bekasi - Shelly Indah Agustina (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
This article has been retracted at the request of publisher.Reason: This article is virtually identical to the previously published article